The therapeutic potential of bacteriophages and endolysins in the treatment of acute respiratory infections caused by bacterial pathogens - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2017)
Bacteriophages are viruses that, due to the receptor/ligand interactions, are able to specifically bind to the bacterial wall and replicate within specific bacteria. The lytic enzymes of bacteriophages efficiently destroy the bacterial cell wall, but unlike antibiotics, they do not affect the vital activity of the symbiotic flora. Today, there is sufficient research experience on the efficacy of antistreptococcal, antistaphylococcal, antiklebsiella, antipseudomonal bacteriophages and endolysins that can kill antibiotic-resistant bacteria, and therefore, their use as bactericidal drugs is a potentially effective therapeutic method of antimicrobial therapy. The high level of effectiveness of the bactericidal action of endolysins suggests that future drugs, created on the molecular basis of endolysins, can become key antimicrobial agents in the treatment of invasive infections.